V2O5-P2O5 Glass Ceramic as a Resistive Solid-State CO2 Gas Sensor - Barde, R.V.; Waghuley, S.A. (Asian Journal of Chemistry, 2012)
Now a day the specific demand for gas detection and monitoring has emerged particularly as the awareness of the need to protect the environment has grown. The solid-state gas sensors, based on a variety of principles and materials, are the best candidates to the development of commercial gas sensors for a wide range of applications. The resistive type solid-state gas sensor of V2O5-P2O5 (1:1 M) glass ceramic was fabricated by melt quenching method on silica substrate. The sensor was investigated for CO2 gas environment at lower ppm level (up to 70 ppm) at room temperature. The response (sensitivity) of sensor at 70 ppm of CO2 was found to be 0.3. The sensing parameters such as resolution limit, resistance change/ppm and response time were observed to be 5.5 ppm, 195 × 106 W/ppm and ca. 2 min respectively. The sensor material was characterized by XRD and SEM analysis.